Macrophage LRP1 Promotes Diet-Induced Hepatic Inflammation and Metabolic Dysfunction by Modulating Wnt Signaling - Au, Dianaly T.; Migliorini, Mary; Strickland, Dudley K.; Muratoglu, Selen C. (Mediators of Inflammation, 2018)
Hepatic inflammation is associated with the development of insulin resistance, which can perpetuate the disease state and may increase the risk of metabolic syndrome and diabetes. Despite recent advances, mechanisms linking hepatic inflammation and insulin resistance are still unclear. The low-density lipoprotein receptor-related protein 1 (LRP1) is a large endocytic and signaling receptor that is highly expressed in macrophages, adipocytes, hepatocytes, and vascular smooth muscle cells. To investigate the potential role of macrophage LRP1 in hepatic inflammation and insulin resistance, we conducted experiments using macrophage-specific LRP1-deficient mice (macLRP1−/−) generated on a low-density lipoprotein receptor knockout (LDLR−/−) background and fed a Western diet. LDLR−/−; macLRP1−/− mice gained less body weight and had improved glucose tolerance compared to LDLR−/− mice. Livers from LDLR−/−; macLRP1−/− mice displayed lower levels of gene expression for several inflammatory cytokines, including Ccl3, Ccl4, Ccl8, Ccr1, Ccr2, Cxcl9, and Tnf, and reduced phosphorylation of GSK3α and p38 MAPK proteins. Furthermore, LRP1-deficient peritoneal macrophages displayed altered cholesterol metabolism. Finally, circulating levels of sFRP-5, a potent anti-inflammatory adipokine that functions as a decoy receptor for Wnt5a, were elevated in LDLR−/−; macLRP1−/− mice. Surface plasmon resonance experiments revealed that sFRP-5 is a novel high affinity ligand for LRP1, revealing that LRP1 regulates levels of this inhibitor of Wnt5a-mediated signaling. Collectively, our results suggest that LRP1 expression in macrophages promotes hepatic inflammation and the development of glucose intolerance and insulin resistance by modulating Wnt signaling.